PROBLEMATIKA PEMBELAJARAN SISWA SD DI TENGAH PERKEMBANGAN ERA GLOBAL DAN DIGITAL PADA SISWA KELAS IV SD NEGERI 057200 BATU MENJAH - Andre Amrizal; Rahma Yanti; Marcella Stephani Panjaitan; Elvi Mailani; Khairunnisa; Abdul Azis Nasution (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
The rapid advancement of globalization and digital technology has significantly influenced various aspects of education, including learning activities at the elementary school level. Along with these developments, students are provided with broader access to information and learning resources. However, the digital era also presents several challenges that may affect the quality of learning. This study aims to examine the learning problems experienced by fourth-grade students at SD Negeri 057200 Batu Menjah in the context of global and digital developments. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that students encounter several challenges, including limited internet access, excessive use of gadgets for non-academic purposes, varying levels of digital literacy, and decreased learning concentration due to digital distractions. In addition, teachers face difficulties in integrating technology effectively into classroom instruction. The study concludes that while digital technology offers valuable opportunities for learning, its implementation requires guidance, supervision, and collaboration among schools, teachers, parents, and students to ensure optimal educational outcomes.